Pharmacological Intervention of Classical Ayurvedic Formulation Chaturbeeja churnam-A Narrative Review Based on Guna Concept - Venkateswaran, Krishnasamy; Patel, Anita (Pharmacognosy Reviews)
Many internal Ayurvedic medicinal herbs are effective in treating Vata rogam, out of these Chaturbeeja churnam (Methika, Chandrashura, Kalajaji, and Yavanika) is one of the combinations (taken internally) described in Bhavaprakasha Nighantu by Bhavprakasha in mishrak gana. The relevant literature was collected from the book source Bhavapraksha Nigandhu, Dravyaguna Vigyan, and Web sources such as Google Scholar, PubMed, Web of Science, Ayush Portal, etc. This article is to explain the therapeutic action of Chaturbeeja churnam in Vatarogam and other diseases with modern comparison. As described in the various treatise of Ayurveda it is mainly working in Vata dosha and other diseases as per text and an attempt is made to correlate some other conditions which are not explained specifically in ayurvedic text with its possible modern diseases. This article discussed the individual ingredient of Chaturbeeja churna for its antispasmodic, analgesic, spasmolytic, and other important activities. It increases the pain threshold and facilitates better pain tolerance capacity. Hope that this review analysis will pave a way for better use of this potent drug to treat various chronic ailments which caused due to alteration in Vata dosham.
Keywords: Chaturbheeja Churnam; Vatharogam; Vatavyadhi; Therapeutic action; Bhavaprakasha nighantu